RESPON FISIOLOGIS ITIK MOJOSARI JANTAN DENGAN PEMBERIAN RANSUM BERKADAR PROTEIN KASAR BERBEDA - Widiawati, Yeni; Sutrisna, Rudy; ., Siswanto (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The purpose of this research is to investigate and evaluate of the physiological responses of Mojosari’s male ducks that given different levels of crude protein (16, 18, 20, or 22% from dry feed). This study has been conducted for 75 days at the Integrated Laboratory Department of Animal Husbandry, of the Agriculture Faculty of the University of Lampung. The total amount of male’s ducks about 48 animals consisted of 16 ducks that is placed in a different plots, so that each plot consists of three male ducks. The male’s ducks are divided into four treatments, which is giving feed in a different protein levels, 16 , 18 , 20 , and 22 % . Each treatment repeated four times. The design of this research using randomized block design and data obtained are analyzed. In conclusion, that ration with crude protein levels of 16, 18, 20, and 22% has no significant effect (P>0.05) on physiological responses of Mojosari’s male ducks and all ration treatment provides the same physiological response ducks on ration levels crude protein 16, 18, 20, and 22%. Keywords: Crude Protein, Feed, Mojosari’s Male Ducks, Physiological Response.